Enhancing Writing Skill in Narrative Text Using Picture Series Media with Genre-Based Approach - Mu’awanah, Risalatul (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
The objective of this classroom action research is to explore how picture series media can improve students’ writing skill in class XI-9 SMA Negeri 14 Semarang. By carrying out 2 cycles, it can be concluded that the using media picture series has been successful and effective. There was an improvement in students’ writing skill in narrative text (legend) according to data from studies on the implementation of picture series media with the using of Genre-Based Approach. The 58,82% increase in average students’ writing skill in cycle 1, which was still lacking, was finally continued with the implementation of cycle 2, which increased by 36,15% from cycle 1. With a percentage increase of 87,87% over the entire cycle, the average student’s writing skill can be scored as good. With two cycles, this study demonstrates that picture series media with using GBA has been successful in improving students’ writing skill. Therefore, another cycle is not required. So it can be concluded that the implementation of using picture series media with using GBS has succeeded in improving students’ writing skill.